Tekanan Sosial dan Pencarian Jati Diri: Krisis Identitas Pada Remaja Otaku (Social Pressure and the Search for Identity: Identity Crisis Among Otaku Adolescents) - Fajarin, Tri Seftian; Lukmawati (Happiness: Journal of Psychology and Islamic Science, 2026)
The increasing involvement of adolescents in the otaku subculture poses complex challenges to their psychosocial identity development. This study aims to analyze the dynamics of identity crises and identify contributing factors among adolescent anime enthusiasts. Utilizing a descriptive qualitative approach, data were collected through interviews, observation, and documentation involving three adolescents experiencing identity confusion. Data analysis followed the Miles and Huberman interactive model, encapaompassing data reduction, data display, and conclusion drawing. The results indicate that identity crises are predominantly driven by social pressures, including stigma and environmental ridicule. Specifically, two informants remain in the exploration stage without firm commitment, while one informant has achieved identity commitment despite facing similar social pressures. Additional exacerbating factors include social media exposure and physical changes during adolescence. These findings emphasize the critical role of social support and environmental acceptance in assisting adolescents to navigate the identity crisis phase healthily.